The cultivation status of Traditional Chinese Medicine nurses in China (中医护理人才培养现状) - LI Jiaji (李佳霁); XU Jingjin (徐京巾); LI Ye (李野); TANG Ling (唐玲) (中西医结合护理)
Traditional Chinese Medicine (TCM) nursing is an important part of TCM. In recent years, the talent team of TCM nursing science has been growing, the quality of employees has been gradually improved, the training of grass-roots talents has been continuously strengthened, and the scientific and technological achievements of high-end talents have becoming more prominent, which plays an increasingly important role in the field of health services and leading the international development of TCM. At the same time, there are some prominent problems, such as the cultivation of high-level academic talents can not meet the needs of nursing discipline development, and the scale of clinical talents is difficult to meet the needs of health services. This paper discussed the development status of talent team in TCM nursing science, so as to provide reference for the construction of TCM nursing talent team. (中医护理是中医药的重要组成部分, 中医护理行业人才队伍不断壮大, 从业人员素质逐步提升, 基层人才培养持续加强, 高端人才科技成果更加突出, 促进行业在健康服务领域、引领中医国际化发展等方面发挥着越来越重要的作用。高层次学术人才培养是护理学科持续发展的重要前提, 本文就中医护理行业人才队伍发展现状进行论述, 为中医护理人才队伍建设提供参考。)